Histogenesis and ultrastructure of pancreatic islet graft microvasculature. Evidence for graft revascularization by endothelial cells of host origin. - Vajkoczy, P. (1995)
In previous studies we have demonstrated that syngeneic and xenogeneic pancreatic islet grafts are revascularized within a 10 to 14-day period after transplantation. With the combined use of intravital and electron microscopy, as well as immunohistochemistry using a set of species-specific or -crossreacting antibodies to endothelial cell antigens, we investigated 1) the origin of the endothelium of the newly formed capillaries in free pancreatic islet isografts (hamster-->hamster) and xenografts (rat-->hamster), and 2) the ultrastructural characteristics of these microvessels. Intravital microscopy demonstrated that newly formed microvessels grow from the vascular bed of the host muscle tissue into the islet grafts. Immunohistochemical analysis of host tissue and transplanted islets with antibodies against factor VIII (recognizing both hamster and rat factor VIII), bovine PECAM-1 (CD31; endoCAM, crossreacting with hamster but not rat PECAM-1), and rat ICAM-1 (CD54, non-crossreacting with hamster ICAM-1) showed that the transplanted rat islets were revascularized by endothelium of hamster (host) origin. At an ultrastructural level, the endothelial lining of the newly formed microvessels showed diaphragmatic fenestration, a characteristic feature of endothelial cells of pancreatic islets in situ. On the basis of these findings we suggest that pancreatic islet transplantation may take a unique position in the field of organ transplantation, since the generally proposed mechanisms of endothelial cell-dependent antigen recognition as a trigger of graft rejection may not be transferred to islet grafts, containing microvessels lined by endothelial cells of host origin.